THE OBJECTIVE SOCIO-ECONOMIC NEED FOR CONSUMER CREDITS TO IMPROVE THE WELL-BEING OF THE COUNTRY’S POPULATION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article analyzes the importance of consumer loans for banking activity, the state of development of the type of activity, the role of consumer loans in improving the well-being of the country’s population, i.e., the issues of improving the consumer credit system, the needs of the population and their current monetary income. Conflicts between the possibility of satisfaction are indicated. The article ends with the author’s suggestions and recommendations for the further development of consumer credit.
Keywords: consumer loan, microloan, microcredit, overdraft loan, credit history, solvency, loan portfolio, financial consumption, consumer loan for goods, education loan, need, welfare.